2008
DOI: 10.1128/aem.02103-07
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial cob and cox1 Genes and Editing of the Corresponding mRNAs in Dinophysis acuminata from Narragansett Bay, with Special Reference to the Phylogenetic Position of the Genus Dinophysis

Abstract: Dinophysis acuminata cells were isolated from Narragansett Bay water samples in June 2005 using flow cytometry. Dinoflagellate-specific PCR primers were used to isolate small-subunit rRNA (18S rRNA), mitochondrial cytochrome b (cob), and cytochrome c oxidase I (cox1) genes and the encoded cDNAs. Maximumlikelihood analysis of a concatenated data set of ribosomal DNA and cDNA sequences of cob and cox1 showed that D. acuminata was sister to Gonyaulacoids, but without strong bootstrap support. The approximately un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 43 publications
1
37
0
Order By: Relevance
“…Recently, the mitochondrial phylogenetic markers cob and cox1, widely used for animal barcoding (Hebert et al, 2003), have proved very useful in delimiting Dinophysis species, at least within the D. acuminata complex (Raho et al, 2008;Zhang et al, 2008;Lin et al, 2009). Raho et al (2008) demonstrated the capacity of cox1 to distinguish D. acuminata from D. ovum.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the mitochondrial phylogenetic markers cob and cox1, widely used for animal barcoding (Hebert et al, 2003), have proved very useful in delimiting Dinophysis species, at least within the D. acuminata complex (Raho et al, 2008;Zhang et al, 2008;Lin et al, 2009). Raho et al (2008) demonstrated the capacity of cox1 to distinguish D. acuminata from D. ovum.…”
Section: Discussionmentioning
confidence: 99%
“…Single or couplets of cells were used for all molecular work, a practice also successfully used in the past (Janson and Graneli, 2003;Raho et al, 2008;Zhang et al, 2008). In the phylogenetic analysis of the rDNA gene region, the sequences obtained in this study co-resided with most sequences assigned to species of the D. acuminata complex onto the well-supported Cluster I.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The editing intensity increases from basal phylogenetic lineages, where it is absent, e.g. in Oxyrrhis marina, to the later branching ones known as the core dinoflagellates (Figure 1; Zhang et al 2008). Although RNA editing occurs in other organisms, the versatility and scale of changes is unprecedented in dinoflagellates.…”
Section: More Peculiarities: Missing Orfs Boundaries Rna Editing Trmentioning
confidence: 99%
“…Genes of mitochondria can act like a molecular clock, and the evolution of mitochondria parallels that of the nucleus; therefore, Cytb has been widely used in studies of phylogenetic analysis in many species, including microalgae (Benne et al, 1986;Bernasconi et al, 2001;Lin et al, 2006). Moreover, Cytb of some species is subject to the phenomenon of RNA editing, which is signifi ed by changes in an RNA sequence compared to that of its encoding DNA (Zanlungo et al, 1993;Islas-Osuna et al, 2006;Zhang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%